TANGGUNG JAWAB BADAN USAHA PERDAGANGAN MELALUI SISTEM ELEKTRONIK DALAM HAL TERJADINYA WANPRESTASI (STUDI KASUS: LAZADA VS ACHMAD SUPARDI) - Nicolas Nicolas; Atalim Atalim (Jurnal Hukum Adigama, 2021)
Recently, the internet is a very important medium in everyday life and provides many benefits, one of which is the emergence of e-commerce. E-commerce itself uses the internet as a medium to provide information about certain goods being sold, such as descriptions of goods, pictures of goods sold, until the price is set by the seller. Although there are many advantages or benefits that people get from buying and selling online or e-commerce, it is not impossible for problems to arise. That arise is a problem in the agreement in the form of default. This default occurred when Achmad Supardi bought 4 motorbikes that were quite cheap, the money had been transferred by Achmad Supardi, but the transaction was canceled by Lazada and the money paid was only replaced in the form of vouchers. After the compensation was given by Lazada, there was a problem, namely the form of compensation provided by Lazada did not match the form that was first transferred by Achmad Supardi. To answer this problem, the writer uses normative research, descriptive research, and secondary data. So the result of this research is the lack of responsibility from Lazada to Achmad Supardi in compensation. Therefore, there is a need for guidelines for transactions in e-commerce.